Higher performance enhancement of direct torque control by using Space Vector Modulation for doubly fed induction machine - Gouaamar Radouan; El Fadl Adiba; Bri Seddik; Mekrini Zineb (E3S Web of Conferences)
This research work aims at current literature review and extensive performance improvement in Direct Torque Control using Space Vector Modulation (DTC-SVM) by considering Doubly Fed Induction Machines. In order to determine the effectiveness of DFIM, significant focus needs to be placed on its speed control design. For highly perturbed systems, traditional Proportional-Integral (PI) speed controllers fail as their gain values are a function of system parameters that inherently change such as engine properties. Therefore, a strong speed controller is necessary to realize high-performance drives. To overcome these confrontations, the proposed study presents backstepping speed control which performs better in terms of accuracy of speed, dynamic tracking and robustness against load disturbances. All proposed control algorithms have been subjected to rigorous tests and simulations using a MATLAB/Simulink environment. A comprehensive study comparing the performance of these speed control within DTC framework is carried out with a detailed insight to important metrics such as dynamic response, reference tracking, torque ripple content involved and complexity among others. This study discusses the pros and cons of all mentioned methods, which helps in better understanding for optimal speed control selection to improve DFIM performance at different operating conditions. The results of this research should help in the further development of control strategies for electric machines to make them more efficient and reliable when used.